Varicella‐Zoster virus ORF9 is an antagonist of the DNA sensor cGAS - Hertzog, J; Zhou, W; Fowler, G; Rigby, RE; Bridgeman, A; Blest, HT; Cursi, C; Chauveau, L; Davenne, T; Warner, BE; Kinchington, PR; Kranzusch, PJ; et al. (EMBO Press, 2022)
Varicella‐Zoster virus (VZV) causes chickenpox and shingles. Although the infection is associated with severe morbidity in some individuals, molecular mechanisms that determine innate immune responses remain poorly defined. We found that the cGAS/STING DNA sensing pathway was required for type I interferon (IFN) induction during VZV infection and that recognition of VZV by cGAS restricted its replication. Screening of a VZV ORF expression library identified the essential VZV tegument protein ORF9 as a cGAS antagonist. Ectopically or virally expressed ORF9 bound to endogenous cGAS leading to reduced type I IFN responses to transfected DNA. Confocal microscopy revealed co‐localisation of cGAS and ORF9. ORF9 and cGAS also interacted directly in a cell‐free system and phase‐separated together with DNA. Furthermore, ORF9 inhibited cGAMP production by cGAS. Taken together, these results reveal the importance of the cGAS/STING DNA sensing pathway for VZV recognition and identify a VZV immune antagonist that partially but directly interferes with DNA sensing via cGAS.